INTELLECTUAL CAPITAL AND ITS IMPACT ON HIGH PERFORMANCE OF ORGANIZATIONS - Latif Abdulridha Atiyah (Journal Park Publishing, 2024)
This study focuses on the impact of the dimensions of Intellectual Capital (IC) which include (Structure-ST, Human-HU, Relational-RE) on the High Performance (HP), of organizations, which includes the dimensions (Participation-PA, Strategic-ST, Efficiency-EF). Information and data for the target sample that the researcher obtained in his study by using a questionnaire form and distributing it to workers in Baghdad Mall / Iraq. Their number was (96), and (4) were incorrect questionnaires, and (92) were valid questionnaires. The researcher used SPSS to reach the basic results of the study. In this study, positive and important results of high quality were proven, and the influence of the dimensions of intellectual capital on high performance in the organization was confirmed. Researcher uses SPSS statistical analysis in this study and (7) point Likert scale. The researcher had broad and useful interests and information in his research, in further expanding the link between the dimensions of intellectual capital and the high performance of organizations.
Keywords: intellectual capital, high performance, structure, Human, Relational.